2023
DOI: 10.1101/2023.01.02.522499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An isogenic human iPSC model unravels neurodevelopmental abnormalities in SMA

Abstract: Whether neurodevelopmental defects underlie the selective neuronal death that characterizes neurodegenerative diseases is becoming an intriguing question. To address it, we focused on the motor neuron (MN) disease Spinal Muscular Atrophy (SMA), caused by reduced levels of the ubiquitous protein SMN. Taking advantage of the first isogenic human induced pluripotent stem cell-derived SMA model that we have generated and a spinal cord organoid system, here we report that the relative and temporal expression of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…These in vitro methods can also be used as powerful platforms for drug testing that may improve the reliability of preclinical trials and decrease dependence on animal experimentation. Moreover, by utilizing differentiation protocols that generate MNs via guiding hiPSCs specification through neural progenitor cell fates, neurodegenerative diseases (NDs) with potentially developmental underlying pathologies can be studied with no ethical hurdles, as has been recently reported for Huntington’s disease [ 124 ] and SMA [ 90 , 108 ]. Additionally, MN co-cultures with other cell types, such as skeletal muscle and microglia, further enable the study of the muscular and inflammatory aspects of MNDs, with a reported critical contribution to disease progression or even initiation [ 125 , 126 , 127 ].…”
Section: 3d Models To Study Neurodegenerative Neuromuscular Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…These in vitro methods can also be used as powerful platforms for drug testing that may improve the reliability of preclinical trials and decrease dependence on animal experimentation. Moreover, by utilizing differentiation protocols that generate MNs via guiding hiPSCs specification through neural progenitor cell fates, neurodegenerative diseases (NDs) with potentially developmental underlying pathologies can be studied with no ethical hurdles, as has been recently reported for Huntington’s disease [ 124 ] and SMA [ 90 , 108 ]. Additionally, MN co-cultures with other cell types, such as skeletal muscle and microglia, further enable the study of the muscular and inflammatory aspects of MNDs, with a reported critical contribution to disease progression or even initiation [ 125 , 126 , 127 ].…”
Section: 3d Models To Study Neurodegenerative Neuromuscular Diseasesmentioning
confidence: 99%
“…In the first study that used SCOs to model SMA, alterations in MNs biogenesis was not observed [ 90 ]. However, by generating the first CRISPR/Cas9-mediated isogenic cohort of SMA corrected hiPSC lines, and following a physiologically relevant SCO model that our group has developed, we recently discovered that markers of NSCs, early pMN and spMNs are significantly reduced and expressed in a temporally abnormal fashion [ 108 ]. In particular, a marked decrease in the expression levels of SOX2 and NESTIN brought forth developmental alterations in NSCs/NPCs as potential initial drivers of SMA pathology [ 108 ] ( Table 2 ).…”
Section: 3d Models To Study Neurodegenerative Neuromuscular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations